ANALISIS HUKUM TERHADAP KEWENANGAN PERADILAN UMUM DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 93/PUU-X/2012 - , RAHMAN HASIMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research on aimed at identifying is the reason birth the authority of general court in the settlement of sharia banking dispute and impact after the decision of the Constitutional Court Number. 93/PUU-X/2012 and legal consequences resulted from the deed containing clauses of dispute settlement through the District Court. This research belongs to a normative research, that was by investigating literature materials or secondary data. They were then analyzed qualitatively. Furthermore, the result of data analysis was presented in descriptive manner, which gave a real description regarding the reason birth the authority of general court in the settlement of sharia banking dispute and impact after the decision of the Constitutional Court Number 93/PUU-X/2012 and legal consequences resulted from the deed containing clauses of dispute settlement through the District Court. Based on the result of analysis, it can be concluded that reason birth the authority of general court in the settlement of sharia banking dispute are economic factors, as transactions in commercial and inability of religious courts in resolving sharia banking disputes. While the impact of posed after the decision of the Constitutional Court Number 93/PUU-X/2012 is no legal binding force, so that the general court not competent then the decision to give legal certainty to customers and sharia banks resolve in sharia banking disputes. Furthermore, the legal consequences resulted from the deed containing the clause of dispute settlement through the District Courth are as follows: 1) if it was issued before the decision of the Constitutional Court, the deed or the agreement is considered valid by law, 2) if it was issued after the decision of the Constitutional Court, the deed or the agreement is declared null and void by law, 3) if the deed or agreement was made before the decision of the Constitutional Court and the dispute occurred after the decision, such deed or agreement is still considered valid because what is considered as the problem is only related to the clause of dispute settlement, called the severability clause. if not then the article regulating the clauses of dispute settlement otherwise has no legal binding force.